2018
DOI: 10.1681/asn.2017111200
|View full text |Cite
|
Sign up to set email alerts
|

NPHP1 (Nephrocystin-1) Gene Deletions Cause Adult-Onset ESRD

Abstract: Nephronophthisis (NPH) is the most prevalent genetic cause for ESRD in children. However, little is known about the prevalence of NPH in adult-onset ESRD. Homozygous full gene deletions of the gene encoding nephrocystin-1 are a prominent cause of NPH. We determined the prevalence of NPH in adults by assessing homozygous full gene deletions in adult-onset ESRD. Adult renal transplant recipients from five cohorts of the International Genetics and Translational Research in Transplantation Network (iGeneTRAiN) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 29 publications
4
73
0
1
Order By: Relevance
“…Albeit rare, other similar patients of NPHP‐induced delayed/adult‐onset ESRD have previously been observed . More recently, 26 (0.5%) patients harboring a homozygous NPHP1 full gene deletion were identified among 5606 patients that underwent kidney transplantation . The average age at which these patients developed ESRD was 30 years (range, 18‐61 years), and 54% of the patients were aged greater than 30 years at ESRD onset.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Albeit rare, other similar patients of NPHP‐induced delayed/adult‐onset ESRD have previously been observed . More recently, 26 (0.5%) patients harboring a homozygous NPHP1 full gene deletion were identified among 5606 patients that underwent kidney transplantation . The average age at which these patients developed ESRD was 30 years (range, 18‐61 years), and 54% of the patients were aged greater than 30 years at ESRD onset.…”
Section: Discussionmentioning
confidence: 91%
“…[10][11][12][13] More recently, 26 (0.5%) patients harboring a homozygous NPHP1 full gene deletion were identified among 5606 patients that underwent kidney transplantation. 5 The average age at which these patients developed ESRD was 30 years (range, 18-61 years), and 54% of the patients were aged greater than 30 years at ESRD onset. In many of these previous reports, the presence of NPHP-modifier genes was discussed as a probable cause of the late ESRD onset.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, previous studies have shown that homozygous deletion of NPHP1, arising from homologous recombination between 45-kilobasepair repeats flanking this gene, is the most frequent mutation observed in familial juvenile nephronophthisis (MIM 256100), a rare progressive tubulointerstitial kidney disorder with autosomal recessive inheritance (28; 29). More than 85% of patients with nephronophthisis, however, are clinically diagnosed as having other nephropathies (52).…”
Section: Discussionmentioning
confidence: 99%